The protein kinase FvRIPK1 regulates plant morphogenesis by ABA signaling using seed genetic transformation in strawberry - Chen, Xuexue; Gu, Xiaojiao; Gao, Fan; Guo, Jiaxuan; Shen, Yuanyue (Frontiers in Plant Science, 2022)
A strawberry RIPK1, a leu-rich repeat receptor-like protein kinase, is previously demonstrated to be involved in fruit ripening as a positive regulator; however, its role in vegetable growth remains unknown. Here, based on our first establishment of Agrobacterium-mediated transformation of germinating seeds in diploid strawberry by FvCHLH/FvABAR, a reporter gene that functioned in chlorophyll biosynthesis, we got FvRIPK1-RNAi mutants. Downregulation of FvRIPK1 inhibited plant morphogenesis, showing curled leaves; also, this silencing significantly reduced FvABAR and FvABI1 transcripts and promoted FvABI4, FvSnRK2.2, and FvSnRK2.6 transcripts. Interestingly, the downregulation of the FvCHLH/ABAR expression could not affect FvRIPK1 transcripts but remarkably reduced FvABI1 transcripts and promoted FvABI4, FvSnRK2.2, and FvSnRK2.6 transcripts in the contrast of the non-transgenic plants to the FvCHLH/FvABAR-RNAi plants, in which chlorophyll contents were not affected but had abscisic acid (ABA) response in stomata movement and drought stress. The distinct expression level of FvABI1 and FvABI4, together with the similar expression level of FvSnRK2.2 and FvSnRK2.6 in the FvRIPK1- and FvABAR/CHLH-RNAi plants, suggested that FvRIPK1 regulated plant morphogenesis probably by ABA signaling. In addition, FvRIPK1 interacted with FvSnRK2.6 and phosphorylated each other, thus forming the FvRIPK1–FvSnRK2.6 complex. In conclusion, our results provide new insights into the molecular mechanism of FvRIPK1 in plant growth.